Impact Behaviour of Laminated Bamboo, E-Glass and Hybrid Bamboo/E-Glass Fibre Composites - Suhaimi, Adam Arif; Ali, Aidy; Rassiah, Kannan; K.Z, Ku Ahmad (International Journal of Integrated Engineering, 2022)
Natural fibres are currently used as a mutually reinforcing fibre foundation. One of their prospects, particularly that which is said to be good in mechanical reinforcement, is bamboo fiber. This study focuses on developing a high-quality bamboo that can withstand high load and high impact application, that utilize and promote green technology and local crops production of bamboo in Malaysia. The work scope was focusing on the impact performance of bamboo fiber as natural fiber, E Glass fiber as synthetic fibers, and combination of both bamboos with E Glass Fiber as hybrid composites. The developed laminated hybrid bamboo was hit by a hard object named impactor in the drop impact testing procedures. The analysis gives the sound of the impact properties that can be absorb with optimal load before the specimen penetrated or failures. Configuration of 6,12,18 layers of woven bamboo and 6,12,18 layers of woven E-Glass, in order of thicknesses 9 mm, 18 mm, 22 mm and 4 mm, 7 mm and 10 mm, respectively were fabricated by hand lay-up. The thickness of each and individual strips of woven bamboo and E-Glass used in the range of 1.5-2.5 mm thicknesses. The results showed that the impact performance of the hybrid bamboo/E-Glass had outperformed the non-hybrid bamboo/E-Glass. The developed hybrid bamboo composites show highly potential use for ballistic application in replacing metal armor.